Answer:
The answer is
Explanation:
use system of equations and substitution.
to solve this equation, one variable needs to be cancelled out to solve for the other.
![-5y+4y=4\\-7y-10x=-10\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/zjnr9caz6htid8fi3g7quprrbxxgbfrvad.png)
looking at this problem, we can manipulate -5 and -7 to equal 35 and -35 to get rid of the variable x to solve for y.
![-7(-5y+4x=4)\\5(-7y-10x=-10)\\\\35y-28x=-28\\-35y-50x=-50](https://img.qammunity.org/2021/formulas/mathematics/high-school/gbkw54y0oo9jcuphmub19hez6zzovu9rmw.png)
with this, we can cancel out 35x and -35x.
![-28x=-28\\-50x=-50](https://img.qammunity.org/2021/formulas/mathematics/high-school/bovpx8jk7yo1pmnj3uzvnah5613gtlof0d.png)
manipulate the equation to equal x.
![x=1\\x=1.](https://img.qammunity.org/2021/formulas/mathematics/high-school/bnkmm4xtrhz3u2nqqh0bxt2aepbzwx5qop.png)
plug 1 for x back into one of the equations to solve for y.
![-5y+4(1)=4\\-5y+4=4\\-5y=0\\y=0](https://img.qammunity.org/2021/formulas/mathematics/high-school/5q0so4u0mflrk8lt4fnrd4r19g7prmgmok.png)
therefore, (1,0)
hope this helps :)